Identification of a divergent genotype of equine arteritis virus from South American donkeys. Issue 6 (17th September 2017) - Rivas, J.; Neira, V.; Mena, J.; Brito, B.; Garcia, A.; Gutierrez, C.; Sandoval, D.; Ortega, R.
Summary: A novel equine arteritis virus (EAV) was isolated and sequenced from feral donkeys in Chile. Phylogenetic analysis indicates that the new virus and South African asinine strains diverged at least 100 years from equine EAV strains. The results indicate that asinine strains belonged to a different EAV genotype.